2000
DOI: 10.1007/s002130000548
|View full text |Cite
|
Sign up to set email alerts
|

Lack of operant ethanol self-administration in dopamine D2 receptor knockout mice

Abstract: Reduced responding in the KO mice for several reinforcers including ethanol indicates a more general role for dopamine D2 receptors in motivated responding rather than a specific role in ethanol reinforcement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 32 publications
4
61
0
Order By: Relevance
“…Thus, by removing the a1 inhibitory GABAergic tone in the VTA, the integrity of the normal downstream GABA/DA circuitry in reinforcing loci such as the nucleus accumbens (NAcc) and the VP is compromised, resulting in an inability of the a1 (À/À) mice to engage in instrumental responding. It is interesting to note that while Phillips et al (1998) found that D2 receptor (À/À) mice were capable of home-cage alcohol drinking (albeit at much lower levels than their D2 ( + / + ) counterparts), Risinger et al (2000) reported that the D2 (À/À) mice demonstrated a profound reduction in EtOH-maintained responding (similar to a1 (À/À) mice in the current study). Hence, a reduction of DA neurotransmission in the a1 (À/À) mice may predispose them to a failure/reduced capacity to initiate lever-press responding for instrumental reinforcers (but see June et al, 2003).…”
Section: Hypothesized Mechanism Of Action In Reducing Etoh and Sucrossupporting
confidence: 47%
“…Thus, by removing the a1 inhibitory GABAergic tone in the VTA, the integrity of the normal downstream GABA/DA circuitry in reinforcing loci such as the nucleus accumbens (NAcc) and the VP is compromised, resulting in an inability of the a1 (À/À) mice to engage in instrumental responding. It is interesting to note that while Phillips et al (1998) found that D2 receptor (À/À) mice were capable of home-cage alcohol drinking (albeit at much lower levels than their D2 ( + / + ) counterparts), Risinger et al (2000) reported that the D2 (À/À) mice demonstrated a profound reduction in EtOH-maintained responding (similar to a1 (À/À) mice in the current study). Hence, a reduction of DA neurotransmission in the a1 (À/À) mice may predispose them to a failure/reduced capacity to initiate lever-press responding for instrumental reinforcers (but see June et al, 2003).…”
Section: Hypothesized Mechanism Of Action In Reducing Etoh and Sucrossupporting
confidence: 47%
“…For example, SA of ethanol increases nucleus accumbens (Nac) DA release in rodents (Weiss et al, 1993(Weiss et al, , 1996Gonzales and Weiss, 1998;Nurmi et al, 1998;Olive et al, 2000;Melendez et al, 2002;Hungund et al, 2003), and DA D1 and D2 receptor agonists and antagonists modulate ethanol SA in some circumstances (Weiss et al, 1990;Hubbell et al, 1991;Dyr et al, 1993;Rassnick et al, 1993a;Ng and George, 1994;Silvestre et al, 1996;Cohen et al, 1998Cohen et al, , 1999Boyce and Risinger, 2002;D'Souza et al, 2003;Zocchi et al, 2003). In addition, genetic deletion of D1 or D2 DA receptors decreases ethanol SA (El-Ghundi et al, 1998;Phillips et al, 1998;Risinger et al, 2000). However, inconsistencies similar to those obtained in examining the DA mediation of opiate reinforcement have plagued the field.…”
Section: Ne and Ethanol Samentioning
confidence: 99%
“…For example, chemical lesions of the NE system, blocking NE synthesis via DBH inhibitors, or genetic deletion of DBH will reduce voluntary ethanol intake, whereas DA lesions do not Kiianmaa et al, 1979;Rassnick et al, 1993b;Weinshenker et al, 2000). Again, evidence does suggest that pharmacologic or genetic manipulation of D1 and D2 receptors can modulate ethanol SA in some circumstances (Weiss et al, 1990;Hubbell et al, 1991;Dyr et al, 1993;Rassnick et al, 1993a;Ng and George, 1994;Silvestre et al, 1996;Cohen et al, 1998Cohen et al, , 1999El-Ghundi et al, 1998;Phillips et al, 1998;Risinger et al, 2000;Boyce and Risinger, 2002;D'Souza et al, 2003;Zocchi et al, 2003). Further research teasing out the specific mechanisms of noradrenergic modulation of opioid and ethanol reward will be required to distinguish between DA-dependent and DA-independent pathways.…”
Section: Some Effects Of Ne On Drug Responses May Be Independent Of Damentioning
confidence: 99%
“…Although this has been studied primarily for psychostimulants such as cocaine and methamphetamine, acute ethanol exposure also increases dopamine release and locomotor activity in rodents (Dar and Wooles, 1984;Imperato and Di Chiara, 1986). Genetic or pharmacologic manipulations that interfere with mesolimbic dopamine systems block not only the stimulant effects of ethanol, but also the rewarding properties (Phillips and Shen, 1996;Phillips et al, 1998;Cunningham et al, 2000;Risinger et al, 2000); however, other neurochemic systems and brain regions are also involved in drug reinforcement (reviewed in Wise, 2000).…”
Section: Role Of Dopaminergic Systems In Acute Ethanol Responses In Dmentioning
confidence: 99%